Gut Microbiota of Young Children Living in Four Brazilian Cities - Chew, Charmaine; Barros, Karina Vieira; Weffort, Virginia Resende Silva; Maranhão, Hélcio de Sousa; Laranjeira, Marisa; Knol, Jan; Roeselers, Guus; de Morais, Mauro Batista (Frontiers in Pediatrics, 2020)
There are several factors (not limited to) that alters the microbiome such as diet, geographical and other environmental influence. In Latin America, there has been lesser microbiome studies especially in young children. In this paper, we investigated the microbiota composition of toddlers in urban settings geographically separated within 4 states of Brazil using 16s RNA gene sequencing. We found alpha diversity to be similar despite living in different cities. Their profiles dominated by Firmicutes and Bacteroidetes, resembled adult microbiota instead of European children of similar age. These findings suggest that inter-individual and nutrition induced differences were apparent in the fecal microbiota. We conclude that urban dietary pattern plays a larger role in influencing the gut microbiota composition compared to geographical differences.